The Utilization of Plant Facilities on the International Space Station—The Composition, Growth, and Development of Plant Cell Walls under Microgravity Conditions - Ann-Iren Kittang Jost; Takayuki Hoson; Tor-Henning Iversen (Plants, 2015)
In the preparation for missions to Mars, basic knowledge of the mechanisms of growth and development of living plants under microgravity (micro-g) conditions is essential. Focus has centered on the g-effects on rigidity, including mechanisms of signal perception, transduction, and response in gravity resistance. These components of gravity resistance are linked to the evolution and acquisition of responses to various mechanical stresses. An overview is given both on the basic effect of hypergravity as well as of micro-g conditions in the cell wall changes. The review includes plant experiments in the US Space Shuttle and the effect of short space stays (8–14 days) on single cells (plant protoplasts). Regeneration of protoplasts is dependent on cortical microtubules to orient the nascent cellulose microfibrils in the cell wall. The space protoplast experiments demonstrated that the regeneration capacity of protoplasts was retarded. Two critical factors are the basis for longer space experiments: a. the effects of gravity on the molecular mechanisms for cell wall development, b. the availability of facilities and hardware for performing cell wall experiments in space and return of RNA/DNA back to the Earth. Linked to these aspects is a description of existing hardware functioning on the International Space Station.